Whole‐body MRI in pediatric undefined inflammatory conditions. Issue 11 (4th October 2021) - Giani, Teresa; Matteoni, Veronica; Perrone, Anna; Simonini, Gabriele; Cimaz, Rolando
Abstract: Background: Whole‐body magnetic resonance imaging (WBMRI) is a multiregional imaging technique suitable for investigating the extent of multisystemic diseases without exposure to radiation, with a high sensitivity to bone alterations. The aim of our study was to evaluate the role of WBMRI in the workup of children with non‐specific musculoskeletal features and non‐indicative laboratory and instrumental data, who were suspected to have a rheumatologic disease. Methods: We retrospectively analyzed medical records, including laboratory tests and radiological data of 34 children who had been evaluated due to non‐specific musculoskeletal manifestations, for which a WBMRI was prescribed. Results: We included 34 children, 19 females and 15 males, mean age 10 years (range 2–16 years), with the following clinical features: diffuse arthralgia (12 children), persistent fever (2 children), persistent fever and diffuse arthralgia (20 children). Serologic inflammatory markers were increased in 29/34 patients. Twenty‐five children had already received X‐ray and / or ultrasound before WBMRI, with a negative / uninformative result. WBMRI was performed 3–6 weeks (median, 3.5 weeks) after the initial presentation of symptoms. In 22/34 (65%) children, WBMRI revealed some abnormalities that supported the final diagnosis. Twelve out of 34 children (35%) were be affected by chronic recurrent multifocal osteomyelitis. Conclusions: WBMRI is helpful in pediatric rheumatology for the differential diagnosis of undefined inflammatory conditions. It appears to be a promising tool, especially in the detection of multifocal bone lesions. The diagnosis that mainly benefits from WBMRI in our series is chronic recurrent multifocal osteomyelitis. WBMRI can also help in excluding neoplastic diseases.